2023
DOI: 10.1111/odi.14553
|View full text |Cite
|
Sign up to set email alerts
|

Burning mouth syndrome: Analysis of diagnostic delay in 500 patients

Abstract: ObjectivesTo assess the diagnostic delay, the number and type of referrals and the clinical and psychological profile in a wide sample of patients with Burning Mouth Syndrome (BMS).Materials and MethodsData on the disease onset, oral symptoms, type and number of practitioners consulted, misdiagnoses, and the presence of medically unexplained extraoral physical symptoms were recorded in 500 BMS patients. Potential predictors of diagnostic delay were also evaluated.ResultsThe mean diagnostic delay was 29.71 ± 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In previous studies, it has been consistently reported that patients affected by Burning Mouth Syndrome (BMS) often experience salivary complaints do not show hyposalivation or hypersalivation regardless of the mensuration methods but may suffer for xerostomia, as well as a subjective sensation of sialorrhea in association with the sensation of burning [7,9,14,15]. These oral symptoms may further complicate the clinical picture making difficult the diagnosis and may increase the discomfort experienced of affected individuals [16].…”
Section: Of 20mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, it has been consistently reported that patients affected by Burning Mouth Syndrome (BMS) often experience salivary complaints do not show hyposalivation or hypersalivation regardless of the mensuration methods but may suffer for xerostomia, as well as a subjective sensation of sialorrhea in association with the sensation of burning [7,9,14,15]. These oral symptoms may further complicate the clinical picture making difficult the diagnosis and may increase the discomfort experienced of affected individuals [16].…”
Section: Of 20mentioning
confidence: 99%
“…BMS is a complex chronic, idiopathic pain disorder characterized by a persistent burning/dysesthetic sensation in the oral cavity, lasting for more than three months in the absence of any local or systemic pathological changes often accompanied by taste alterations and oral discomfort [17]. The presence of xerostomia and subjective sensation of sialorrhea in BMS patients, sometimes simultaneously associated seems to be a contradictory association highlighting the intricate nature of BMS and emphasizes the need for a comprehensive understanding of the underlying mechanisms [7,16]. Exploring the relationship between xerostomia, sialorrhea, and the burning sensation in BMS can provide valuable insights into the pathophysiology of this syndrome and contribute to more effective diagnostic and therapeutic approaches.…”
Section: Of 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Several additional oral and extraoral symptoms have been reported, with burning negatively affecting the psychological profile and quality of life of such patients [18]. Mood disorders, sleep disturbance, and cognitive impairment frequently overlap with BMS, contributing to the aggravation of the disease [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the initial trigger, the prevalence of anxiety and depression is around of 35–45% in several chronic and disabling pain conditions such as fibromyalgia, low back pain, irritable bowel syndrome, migraines, temporomandibular disorders, and burning mouth syndrome (Meda et al, 2022 ; Adamo et al, 2023 ) where mood disorders may not only contribute to pain intensity, but also predict the onset of dementia 25 years in advance with a consequent increased risk of disability for the patients (Ly et al, 2021 ).…”
mentioning
confidence: 99%